PELAKSANAAN TANGGUNG JAWAB DALAM PENGANGKUTAN BARANG LAUT PADA PELABUHAN JAYA PEKANBARU - IRWAN PARDEDE; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Organizing activities in the sea transport of goods held for their agreement and the legal relationship between several parties , namely the owner of the goods , forwarder , carrier and entrepreneur ship . The parties involved in transport in the waters being responsible for the safety and security of goods are removed according to the type and amount stated in the charge documents and / or the agreement or contract of carriage has been agreed as Article 40 of Law Number 17 , 2008. The responsibilities arising as a result of the operation of the ship, destroyed , lost , or damage to the goods transported , delay in transportation of passengers and / or freight . Based on the above , the problems regarding the implementation of the author adopted is the responsibility of the parties in case of damaged / lost and delays caused by faults and constraints faced by the owners / shippers against the losses suffered. This type of research the authors classified into types of sociological research by looking at the correlation between the law society , so as to reveal the effectiveness of the rule of law in society and to identify the unwritten law in force in the community who do on-site research that is how the implementation of the responsibilities of the parties in the transport Jaya marine goods at the Port of Pekanbaru .Implementation of the responsibilities of the parties in the transport of goods by sea at the Port of Pekanbaru Jaya should run properly with in accordance with agreements made and provisions of the Act in force and on the implementation of these responsibilities , difficulties . The problem that often occurs is when the goods are shipped owner of the goods were damaged / lost and delays caused by the parties in the transport , lack of information about the procedures in filing losses to the owner of the goods and the lack of legal awareness of the parties in the transport .Keywords : Responsibility - The Parties - Sea Transport Cargo